KESEJAHTERAAN PSIKOLOGIS PADA SISWA TANPA PERAN AYAH DI SMK NEGERI 4 SURAKARTA - Charisma, Nafisah; Riskiana Putri, Dhian; Rachmawati Musslifah, Anniez (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to explore the dynamics of psychological well-being among fatherless students at SMK Negeri 4 Surakarta. Using a qualitative method, data were collected through in-depth interviews with seven fatherless students and on guidance and counseling teacher. The results indicate that the students are capable of achieving adaptive psychological well-being across Ryff's six dimensions. Self-acceptance is attained by resolving past conflicts, while positive relations with others rely heavily on the mother figure as the primary pillar. Autonomy develops rapidly as a compensation for the father's absence, and environmental mastery is evident in the ability to manage dual roles between school and work. Students goals in life are identified as concrete and family-oriented, supported by personal growth through vocational education. It is concluded that despite facing emotional vulnerability, fatherless students demonstrate high resilience, where autonomy and purpose in life serve as the main balancing strengths in maintaining their mental health.